(untitled) (Journal of Engineering, 2025)
This study numerically investigates the effect of different welding steel plate shapes on the behavior of expanded open web asymmetrical steel composite beams. Increased web depth of asymmetrical steel beams in composite concrete results in increased stiffness and strength. Expanding the web’s depth enhances the composite concrete steel beam’s strength and performance in specific design scenarios, such as expanded, cellular, or castellated steel composite concrete beams. A horizontal cut in the web in each asymmetrical section can create an expanded web of asymmetrical steel profiles. Two asymmetrical tees can then be assembled, and a plate known as a spacer plate with a constant area and different shapes can be added between the two halves of the asymmetrical tee sections. The Finite Element (FE) numerical model developed by ABAQUS software was employed to develop and evaluate new numerical models by considering a variety of increment plate configurations, which resulted in the production of a greater number of models at a lower cost and more efficiently. The results indicate that curved plates increased the ultimate load capacity, while other shapes led to decreased stiffness. Therefore, the ultimate load capacity of the curved plate increased by approximately 2.3% compared to the reference model due to a reduced stress distribution.